2020
DOI: 10.1073/pnas.2011763118
|View full text |Cite
|
Sign up to set email alerts
|

UFMylation inhibits the proinflammatory capacity of interferon-γ–activated macrophages

Abstract: Macrophages activated with interferon-γ (IFN-γ) in combination with other proinflammatory stimuli, such as lipopolysaccharide or tumor necrosis factor-α (TNF-α), respond with transcriptional and cellular changes that enhance clearance of intracellular pathogens at the risk of damaging tissues. IFN-γ effects must therefore be carefully balanced with inhibitory mechanisms to prevent immunopathology. We performed a genome-wide CRISPR knockout screen in a macrophage cell line to identify negative regulators of IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 67 publications
1
29
0
Order By: Relevance
“…The ATG5-12-16L1 complex is crucial for IFNγ-induced control of MNoV CW3 in bone marrow-derived murine macrophages (11). Using Atg5 knockout BV-2 cells ( Atg5 -/- ) (26, 27) we confirmed that Atg5 was required for IFNγ-induced inhibition of MNoV CW3 replication (Fig. 1C).…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…The ATG5-12-16L1 complex is crucial for IFNγ-induced control of MNoV CW3 in bone marrow-derived murine macrophages (11). Using Atg5 knockout BV-2 cells ( Atg5 -/- ) (26, 27) we confirmed that Atg5 was required for IFNγ-induced inhibition of MNoV CW3 replication (Fig. 1C).…”
Section: Resultsmentioning
confidence: 57%
“…Certain upstream components of the autophagy pathway are not required for IFNγ-induced inhibition of norovirus or T. gondii replication (10, 11, 15, 16). To confirm these observations in BV-2 cells, we determined whether IFNγ efficiently inhibits MNoV CW3 replication in clonal Atg14 -/- BV-2 cells (26, 27) and clonal Becn1 -/- cell lines (27). Neither Atg14 nor Becn1 were required for IFNγ-induced inhibition of MNoV CW3 replication (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations